3D correlative morphological and elemental characterization of materials at the deep submicrometre scale. (11th August 2016) - PRIEBE, A.; GORET, G.; BLEUET, P.; AUDOIT, G.; LAURENCIN, J.; BARNES, J.‐P.
Summary: This paper shows how X‐ray computed nanotomography (CNT) can be correlated with focused ion beam time‐of‐flight secondary ion mass spectrometry (FIB‐TOF‐SIMS) tomography on the same sample to investigate both the morphological and elemental structure. This methodology is applicable to relatively large specimens with dimensions of several tens of microns whilst maintaining a high spatial resolution of the order of 100 nm. However, combining X‐ray CNT and FIB‐TOF‐SIMS tomography requires innovative sample preparation protocols to allow both experiments to be conducted on exactly the same sample without chemically or structurally modifying the sample between measurements. Moreover, dedicated algorithms have been developed for effective data fusion that is biased with nine degrees of freedom. This methodology has been tested using a porous and heterogeneous solid oxide fuel cell (SOFC) that has features varying in size by three orders of magnitude – from hundreds of nanometre large pores and grains to tens of micron wide functional layers.